Preparation method of diaphragm of secondary battery and secondary battery
By silane modification and electrospinning preparation of the lithium-ion battery separator, combined with highly thermal conductivity and high elasticity modified materials, the problems of excessive expansion force and poor heat dissipation of the battery cell during charging and discharging of lithium-ion batteries are solved, and higher energy density and safety are achieved.
Patent Information
- Application Number
- CN202510309200.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-14
AI Technical Summary
During the charging and discharging process of lithium-ion batteries, the expansion force of the battery cell is too large and bulging due to volume expansion, and the problem of poor heat dissipation.
By silane modification of the base film and inorganic particles, and mixing the raw materials including elastic polymer, modified inorganic particles, modified base film, chain extender and organic solvent, electrospinning was performed to prepare the separator. The modified inorganic particles have high thermal conductivity, the elastic polymer has high elasticity and elongation, and the silane-modified base film improves the composite effect.
It alleviates the expansion force of the lithium-ion battery and the expansion force of the battery cell during charging and discharging overcharging, improves the thermal conductivity of the diaphragm, reduces the risk of temperature concentration and thermal runaway of the battery cell, and thus improves the energy density and safety of the battery cell.
Smart Images

Figure CN119824609A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a secondary battery diaphragm and a secondary battery. Background Art
[0002] At present, battery cell products are developing in the direction of large capacity, high energy density and high safety. The method to achieve high energy density batteries is mainly through the development of higher compaction, high gram capacity positive and negative electrode materials, and by optimizing the internal space layout of the battery cell, so as to achieve the design of high energy density lithium-ion batteries as much as possible. However, the performance of positive and negative electrode materials has been close to the theoretical performance, and the optimization of the internal space of the battery cell is relatively reasonable. In order to further achieve higher energy density, it is necessary to find new optimization directions.
[0003] During the charging and discharging process, lithium-ion batteries still have problems such as excessive cell expansion force and bulging due to volume expansion. In addition, large-capacity batteries are prone to uneven temperature distribution and high local temperatures during normal operation, which leads to the attenuation of cell performance. At the same time, when large-capacity batteries are out of control, higher energy release will occur, making it more likely to have safety issues such as cell fire and explosion. For the safety issues of large-capacity cells, the current main approach is to regulate the electrolyte composition, and to suppress thermal runaway of the cell by adding flame retardants and other ingredients. However, regulating the electrolyte composition will reduce the electrochemical performance of the cell to a certain extent, and it cannot solve the problems of uneven temperature distribution and heat dissipation of large-capacity cells during the charging and discharging process. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for preparing a secondary battery diaphragm and a secondary battery to solve the problems of excessive cell expansion force and bulging and poor heat dissipation caused by volume expansion during charge and discharge and overcharge of lithium-ion batteries in the prior art.
[0005] In order to achieve the above-mentioned object, according to one aspect of the present invention, a method for preparing a secondary battery diaphragm is provided, the preparation method comprising: step S1, silane-modifying a base film and inorganic particles respectively to obtain a modified base film and modified inorganic particles; step S2, mixing raw materials including an elastic polymer, modified inorganic particles, a modified base film, a chain extender and an organic solvent to obtain a spinning precursor solution; step S3, electrostatically spinning the spinning precursor solution to obtain a diaphragm; wherein the base film is polyethylene and / or polypropylene; the elastic polymer is a polyurethane polymer; the thermal conductivity of the modified inorganic particles is 35~200W / (m·K); the inorganic particles are aluminum oxide and / or aluminum nitride; when the inorganic particles are a combination of aluminum oxide and aluminum nitride, the mass ratio of aluminum oxide to aluminum nitride is 1:1~1:2; and / or the chemical formula of the polyurethane polymer is , where n is 10~35.
[0006] Furthermore, in the above step S2, the mass ratio of the modified base film, the modified inorganic particles and the elastic polymer is 50-75:5-10:25-40.
[0007] Furthermore, the mass ratio of the elastic polymer to the modified base film is 25-35:55-70; and / or the elongation of the elastic polymer is 400-700%.
[0008] Furthermore, the above step S1 also includes: ball milling the inorganic particles to obtain ball-milled particles; mixing the ball-milled particles and water, and then centrifugally dispersing, washing and first drying in sequence to obtain pretreated inorganic particles; wherein the ball milling speed is 500~600r / min, and / or the ball milling time is 12~20h; and / or the first drying temperature is 80~100°C, and / or the first drying time is 24~36h.
[0009] Furthermore, the above-mentioned step S1 also includes: using a silane coupling agent to modify the base film and the pre-treated inorganic particles respectively, and the modification treatment includes silane modification and second drying performed in sequence; wherein the silane coupling agent is selected from any one or more of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane; and / or, the silane modification temperature is 80~150°C, and the silane modification time is 4~6h; and / or, the second drying temperature is 100~130°C, and / or, the second drying time is 2~4h.
[0010] Furthermore, in the above step S2, the preparation method of the elastic polymer includes: subjecting polytetrahydrofuran ether diol to a first heating, a first vacuum dehydration and a cooling in sequence to obtain pretreated polytetrahydrofuran ether diol; subjecting the pretreated polytetrahydrofuran ether diol and diphenylmethane diisocyanate to a polymerization reaction to obtain an elastic polymer; wherein the molecular weight of the polytetrahydrofuran ether diol is 1000-3000; and / or the first heating temperature is 110-120°C; and / or the first vacuum dehydration negative pressure is 0.1-0.3MPa, and the first vacuum dehydration time is 2-4h; and / or the cooling temperature is 60-80°C; and / or the polymerization reaction temperature is 80-100°C, and the polymerization reaction time is 40-100min; and / or the molar ratio of the pretreated polytetrahydrofuran ether diol and diphenylmethane diisocyanate is 2-4:1.
[0011] Furthermore, the above-mentioned step S2 also includes: sequentially performing a second heating and a second vacuum dehydration on the raw materials including the elastic polymer, the modified inorganic particles, the modified base film and the organic solvent to obtain a first mixture; sequentially stirring, degassing and centrifuging the raw materials including the first mixture and the chain extender to obtain a spinning precursor solution; wherein the organic solvent is N,N-dimethylacetamide; and / or the second heating temperature is 75~85°C; and / or the second vacuum dehydration negative pressure is 0.1~0.3MPa, and the second vacuum dehydration time is 1.5~4; and / or the mass ratio of the first mixture and the chain extender is 97~99:1~3; and / or the chain extender is a diamine compound, and the diamine compound is selected from any one or more of ethylenediamine, 3,3-dichloro-4'-diaminodiphenylmethane and hydroxypropyl acrylate; and / or the stirring speed is 3000~5000rpm, and the stirring time is 10~20min.
[0012] Furthermore, in the above step S2, the ratio of the total mass of the elastic polymer, the modified inorganic particles and the modified base film to the volume of the organic solvent is 20-40:100 g / mL.
[0013] Furthermore, in the above step S3, the spinning precursor liquid is sucked into the needle tube for electrospinning; wherein the suction speed is 0.3~0.6mL / h; and / or the voltage of electrospinning is 18~25kV, and / or the spinning roller speed of electrospinning is 200~300r / min.
[0014] According to another aspect of the present invention, a secondary battery is provided, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is obtained by the above-mentioned preparation method, and the thickness of the separator is 12-15 μm.
[0015] By applying the technical solution of the present invention, the present application can improve the composite effect between the silane-modified base film, the silane-modified inorganic particles and the elastic polymer by silane-modifying the base film and the inorganic particles respectively in step S1. By adding the modified base film of the above type to the raw material in step S2, it has the characteristics of high strength and good processing performance. The elastic polymer of the above type has extremely high elasticity and high elongation. It can quickly recover to its original length during the stretching process. The elastic polymer is compounded with the modified base film, which can improve the resilience of the diaphragm while ensuring the strength of the diaphragm, thereby alleviating the excessive expansion force and bulging of the battery cell caused by volume expansion during overcharging of the lithium-ion battery during charge and discharge, and can also relax the design group margin and improve the energy density of the battery cell. It is preferred that the elastic polymer is the above-mentioned polyurethane polymer, which can further improve the resilience of the diaphragm and better compound with the modified base film and the modified inorganic particles. The thermal conductivity of the modified inorganic particles is in the above range, which is much greater than the thermal conductivity of the base film (0.13~0.5W / (m·K)). Therefore, the addition of the modified inorganic particles can greatly improve the thermal conductivity of the diaphragm. Specifically, the modified inorganic particles can effectively conduct the heat of the battery cell during the charging and discharging process, thereby reducing the battery cell performance degradation caused by temperature concentration during the battery cell testing process, and can also reduce the risk of fire and explosion of the battery cell during thermal runaway. The addition of a chain extender can increase the length and cross-linking density of the polymer chain, thereby improving the performance of the diaphragm. The electrospinning process of step S3 can better regulate the morphology, structure and performance of the diaphragm. Therefore, the diaphragm obtained by the preparation method of the present application has high elasticity and high thermal conductivity, which provides a material basis for designing high energy density and safe lithium-ion batteries. DETAILED DESCRIPTION
[0016] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0017] As analyzed in the background technology of the present application, the prior art has problems such as excessive expansion force and bulging of the battery cell as well as poor heat dissipation due to volume expansion during charge and discharge and overcharge of lithium-ion batteries. In order to solve the above problems, the present application provides a method for preparing a secondary battery diaphragm and a secondary battery.
[0018] In a typical embodiment of the present application, a method for preparing a secondary battery diaphragm is provided, the preparation method comprising: step S1, silane-modifying a base film and inorganic particles respectively to obtain a modified base film and modified inorganic particles; step S2, mixing raw materials including an elastic polymer, modified inorganic particles, a modified base film, a chain extender and an organic solvent to obtain a spinning precursor solution; step S3, electrostatically spinning the spinning precursor solution to obtain a diaphragm; wherein the base film is polyethylene and / or polypropylene; the elastic polymer is a polyurethane polymer; the thermal conductivity of the modified inorganic particles is 35~200W / (m·K); the inorganic particles are aluminum oxide and / or aluminum nitride; when the inorganic particles are a combination of aluminum oxide and aluminum nitride, the mass ratio of aluminum oxide to aluminum nitride is 1:1~1:2;
[0019] In one embodiment of the present application, the chemical formula of the polyurethane polymer is , where n is 10~35.
[0020] The present application can improve the composite effect between the silane-modified base film, the silane-modified inorganic particles and the elastic polymer by silane-modifying the base film and the inorganic particles respectively in step S1. The modified base film of the above type is added to the raw material in step S2, which has the characteristics of high strength and good processing performance. The elastic polymer of the above type has extremely high elasticity and high elongation. It can quickly recover to its original length during the stretching process. The elastic polymer is compounded with the modified base film, which can improve the resilience of the diaphragm while ensuring the strength of the diaphragm, thereby alleviating the excessive expansion force and bulging of the battery cell caused by volume expansion during overcharging of the lithium-ion battery during charge and discharge, and can also relax the design group margin and improve the energy density of the battery cell. It is preferred that the elastic polymer is the above-mentioned polyurethane polymer, which can further improve the resilience of the diaphragm and better compound with the modified base film and the modified inorganic particles. The thermal conductivity of the modified inorganic particles is in the above range, which is much greater than the thermal conductivity of the base film (0.13~0.5W / (m·K)). Therefore, the addition of the modified inorganic particles can greatly improve the thermal conductivity of the diaphragm. Specifically, the modified inorganic particles can effectively conduct the heat of the battery cell during the charging and discharging process, thereby reducing the battery cell performance degradation caused by temperature concentration during the battery cell testing process, and can also reduce the risk of fire and explosion of the battery cell during thermal runaway. The addition of a chain extender can increase the length and cross-linking density of the polymer chain, thereby improving the performance of the diaphragm. The electrospinning process of step S3 can better regulate the morphology, structure and performance of the diaphragm. Therefore, the diaphragm obtained by the preparation method of the present application has high elasticity and high thermal conductivity, which provides a material basis for designing high energy density and safe lithium-ion batteries.
[0021] In addition, in the general chemical formula of the polyurethane polymer, n can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34 or 35. Of course, n can be any point value within the range of 10 to 35, which will not be repeated here.
[0022] Preferably, n in the chemical formula of the polyurethane polymer is 20 to 35. The longer the molecular chain of the polyurethane with a high degree of polymerization is, the higher the strength and elasticity are.
[0023] In one embodiment of the present application, in the above step S2, the mass ratio of the modified base film, the modified inorganic particles and the elastic polymer is 50~75:5~10:25~40.
[0024] It is preferred to control the mass ratio of the modified base film, the modified inorganic particles and the elastic polymer within the above range, which helps to make the separator have sufficient strength and improve elasticity, so as to better adapt to the volume change of the electrode material, reduce the internal stress caused by the expansion of the battery cell, avoid battery bulging, and thus improve the cycle stability and life of the battery. At the same time, the appropriate amount of inorganic particles helps to further improve the thermal conductivity of the separator, reduce the risk of local overheating, and thus improve the overall safety and thermal performance of the battery.
[0025] In one embodiment of the present application, the mass ratio of the elastic polymer to the modified base film is 25-35:55-70; and / or the elongation of the elastic polymer is 400-700%.
[0026] It is preferred to control the mass ratio of the elastic polymer and the modified base film and the elongation of the elastic polymer within the above range, which helps to better compound the elastic polymer and the modified base film, thereby further improving the resilience of the diaphragm, thereby alleviating the excessive expansion force and bulging of the battery cell caused by volume expansion during charge and discharge and overcharge of the lithium-ion battery.
[0027] In one embodiment of the present application, the above-mentioned step S1 also includes: ball milling the inorganic particles to obtain ball-milled particles; mixing the ball-milled particles and water, and then centrifugally dispersing, washing and first drying in sequence to obtain pretreated inorganic particles; wherein the ball milling speed is 500~600r / min, and / or the ball milling time is 12~20h; and / or the first drying temperature is 80~100℃, and / or the first drying time is 24~36h.
[0028] Preferably, the inorganic particles are ball-milled, and the speed and time of ball milling are controlled within the above range, which helps to reduce the particle size of the inorganic particles, thereby increasing the contact area between the inorganic particles and the base film, and then improving the thermal conductivity of the diaphragm. In addition, the ball milling process also helps to change the morphology of the inorganic particles, making them have a more uniform shape, which is conducive to subsequent dispersion and compounding. Preferably, the particles and water after ball milling are subjected to the above treatment, and the temperature and time of the first drying are controlled within the above range, which helps to remove impurities on the surface of the particles, and at the same time makes the particles more evenly dispersed in the solution, providing a better basis for subsequent surface modification and compounding.
[0029] In one embodiment of the present application, the above-mentioned step S1 also includes: using a silane coupling agent to modify the base film and the pre-treated inorganic particles respectively, and the modification treatment includes silane modification and second drying performed in sequence; wherein the silane coupling agent is selected from any one or more of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane; and / or, the silane modification temperature is 80~150°C, and the silane modification time is 4~6h; and / or, the second drying temperature is 100~130°C, and / or, the second drying time is 2~4h.
[0030] It is preferred to use the above-mentioned types of silane coupling agents to modify the base film and the pretreated inorganic particles respectively, and control the temperature and time of silane modification within the above-mentioned range, which helps to fully silane-modify the surfaces of the base film and the inorganic particles, thereby alleviating the problem of interface incompatibility, improving the distribution uniformity of the components of the diaphragm, and further enhancing the composite effect between the silane-modified base film, the silane-modified inorganic particles and the elastic polymer.
[0031] In one embodiment of the present application, in the above-mentioned step S2, the preparation method of the elastic polymer includes: subjecting polytetrahydrofuran ether diol to a first heating, a first vacuum dehydration and a cooling in sequence to obtain pretreated polytetrahydrofuran ether diol; subjecting the pretreated polytetrahydrofuran ether diol and diphenylmethane diisocyanate to a polymerization reaction to obtain an elastic polymer; wherein the molecular weight of the polytetrahydrofuran ether diol is 1000~3000; and / or, the temperature of the first heating is 110~120°C; and / or, the negative pressure of the first vacuum dehydration is 0.1~0.3MPa, and the time of the first vacuum dehydration is 2~4h; and / or, the cooling temperature is 60~80°C; and / or, the temperature of the polymerization reaction is 80~100°C, and the time of the polymerization reaction is 40~100min; and / or, the molar ratio of the pretreated polytetrahydrofuran ether diol and diphenylmethane diisocyanate is 2~4:1.
[0032] Preferably, the elastic polymer is prepared by the above preparation method, and the molecular weight of tetrahydrofuran ether diol is controlled within the above range, which helps to regulate the molecular weight and molecular chain length of the elastic polymer, thereby better compounding with the base film and inorganic particles.
[0033] In one embodiment of the present application, the above-mentioned step S2 also includes: sequentially performing a second heating and a second vacuum dehydration on the raw materials including the elastic polymer, the modified inorganic particles, the modified base film and the organic solvent to obtain a first mixture; sequentially stirring, degassing and centrifuging the raw materials including the first mixture and the chain extender to obtain a spinning precursor solution; wherein the organic solvent is N,N-dimethylacetamide; and / or, the temperature of the second heating is 75~85°C; and / or, the negative pressure of the second vacuum dehydration is 0.1~0.3MPa, and the time of the second vacuum dehydration is 1.5~4; and / or, the mass ratio of the first mixture and the chain extender is 97~99:1~3; and / or, the chain extender is a diamine compound, and the diamine compound is selected from any one or more of ethylenediamine, 3,3-dichloro-4'-diaminodiphenylmethane (MOCA) and hydroxypropyl acrylate (HPA); and / or, the stirring speed is 3000~5000rpm, and the stirring time is 10~20min.
[0034] In one embodiment of the present application, in the above step S2, the ratio of the total mass of the elastic polymer, the modified inorganic particles and the modified base film to the volume of the organic solvent is 20-40:100 g / mL.
[0035] It is preferred to control the total mass ratio of the elastic polymer, modified inorganic particles and modified base membrane to the volume of the organic solvent within the above range, which helps the elastic polymer, modified inorganic particles and modified base membrane to be better dispersed in the organic solvent, thereby better compounding the three and improving the distribution uniformity of the components of the diaphragm.
[0036] In one embodiment of the present application, in the above step S3, the spinning precursor liquid is sucked into the needle tube for electrospinning; wherein the suction speed is 0.3~0.6mL / h; and / or the voltage of electrospinning is 18~25kV, and / or the spinning roller speed of electrospinning is 200~300r / min.
[0037] Preferably, the spinning precursor solution is sucked into the needle tube for electrospinning, and the suction speed, the electrospinning voltage and the spinning roller speed are controlled within the above range, which helps to improve the uniformity of fiber distribution during the electrospinning process, thereby obtaining a denser and more uniform diaphragm structure, thereby improving the stability and reliability of the diaphragm in the battery. Adjusting the electrospinning voltage helps to control the diameter of the fiber, thereby regulating the porosity and pore size distribution of the diaphragm.
[0038] In another typical embodiment of the present application, a secondary battery is provided, comprising a positive electrode plate, a negative electrode plate and a separator, wherein the separator is obtained by the above preparation method, and the thickness of the separator is 12-15 μm.
[0039] The secondary battery including the above separator has good cycle performance, cycle life and safety performance.
[0040] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0041] Example 1
[0042] Preparation of elastic polymer: Pour polytetrahydrofuran ether diol into a reaction vessel and heat it to 115°C for the first time, perform the first vacuum dehydration for 2 hours under a negative pressure of 0.1 MPa, and then cool it to 60°C to obtain pretreated polytetrahydrofuran ether diol. In an atmosphere of protective gas, heat the pretreated polytetrahydrofuran ether diol and diphenylmethane diisocyanate to 90°C for polymerization for 40 minutes, and vacuum degas for 30 minutes to obtain an elastic polymer. Among them, the molar ratio of pretreated polytetrahydrofuran ether diol and diphenylmethane diisocyanate is 2:1. The elastic polymer is , n is 35.
[0043] Pretreatment of inorganic particles: 5 g of aluminum oxide and 10 g of aluminum nitride were mixed and added to a ball mill and solid-phase ball milled at 550 r / min for 15 h to obtain ball-milled particles. The ball-milled particles were dispersed in 500 mL of deionized water, washed with water several times after centrifugation, and dried in a vacuum oven at 90°C for 30 h to obtain pretreated inorganic particles.
[0044] Preparation of modified base film and modified inorganic particles: The base film polyethylene and the pretreated inorganic particles were modified respectively using a silane coupling agent γ-aminopropyltriethoxysilane, and the modification treatment included silane modification at 120°C for 5 hours and a second drying at 110°C for 3 hours to obtain a modified base film and modified inorganic particles.
[0045] Preparation of the diaphragm: Add 20g of elastic polymer, modified inorganic particles and modified base film (the mass ratio of the three is 25:5:70) to 100mL of N,N-dimethylacetamide for the second heating to 80°C, and perform the second vacuum dehydration for 1.5h under a negative pressure of 0.1MPa to obtain a first mixture. Add 0.5g of the pre-melted chain extender ethylenediamine to the first mixture and stir at 4000rpm for 10min with an electric stirrer, followed by degassing and centrifugation to obtain a spinning precursor solution. The spinning precursor solution is absorbed into a needle tube, and electrospinning is performed under the conditions of a voltage of 18kV, an absorption speed of 0.3mL / h, and a spinning roller speed of 200r / min to obtain a spun diaphragm. The spun diaphragm is placed in a vacuum oven for drying to obtain a diaphragm with a thickness of 12μm.
[0046] Example 2
[0047] The difference from Example 1 is that the elastic polymer is , n is 20, and finally a diaphragm is obtained.
[0048] Example 3
[0049] The difference from Example 1 is that the mass ratio of the elastic polymer, the modified inorganic particles and the modified base film is 40:5:55, and a separator is finally obtained.
[0050] Example 4
[0051] The difference from Example 1 is that the mass ratio of the elastic polymer, the modified inorganic particles and the modified base film is 25:10:65, and a separator is finally obtained.
[0052] Example 5
[0053] The difference from Example 1 is that the mass ratio of the elastic polymer, the modified inorganic particles and the modified base film is 40:10:50, and a separator is finally obtained.
[0054] Example 6
[0055] The difference from Example 1 is that the mass ratio of the elastic polymer, the modified inorganic particles and the modified base film is 15:15:70, and a separator is finally obtained.
[0056] Example 7
[0057] The difference from Example 1 is that the temperature of silane modification is 80° C., the time of silane modification is 6 hours, and a modified base film and modified inorganic particles are obtained, and finally a separator is obtained.
[0058] Example 8
[0059] The difference from Example 1 is that the temperature of silane modification is 60° C., the time of silane modification is 2 h, and a modified base film and modified inorganic particles are obtained, and finally a separator is obtained.
[0060] Example 9
[0061] The difference from Example 1 is that the voltage of electrospinning is 25 kV, the spinning roller speed of electrospinning is 300 r / min, and finally a diaphragm is obtained.
[0062] Example 10
[0063] The difference from Example 1 is that the voltage of electrospinning is 15 kV, the spinning roller speed of electrospinning is 350 r / min, and finally a diaphragm is obtained.
[0064] Comparative Example 1
[0065] Using polyethylene as the substrate, a 7+2+2 thick Al2O3-containing glue-coated diaphragm is obtained, wherein the thickness of the polyethylene base film is 7 μm, the thickness of the glue layer covering one side of the base film is 2 μm, and the thickness of the Al2O3 ceramic coating covering the other side is 2 μm.
[0066] Comparative Example 2
[0067] The difference from Example 1 is that the elastic polymer is , n is 6, and finally a diaphragm is obtained.
[0068] Comparative Example 3
[0069] The difference from Example 1 is that no inorganic particles are added, and a total mass of 20 g of the elastic polymer and the modified base membrane (the mass ratio of the two is 30:70) is added to 100 mL of N,N-dimethylacetamide for a second heating to 80°C, and a second vacuum dehydration is performed at a negative pressure of 0.1 MPa for 1.5 hours to obtain a first mixture, and finally a diaphragm is obtained.
[0070] Comparative Example 4
[0071] The difference from Example 1 is that no elastic polymer is added, and a total mass of 20 g of modified inorganic particles and modified base membrane (the mass ratio of the two is 30:70) is added to 100 mL of N,N-dimethylacetamide for a second heating to 80°C, and a second vacuum dehydration is performed at a negative pressure of 0.1 MPa for 1.5 hours to obtain a first mixture, and finally a diaphragm is obtained.
[0072] Comparative Example 5
[0073] The difference from Example 1 is that the inorganic particles and the base film are not subjected to silane modification, and a separator is finally obtained.
[0074] Test method:
[0075] The separators of the above embodiments and comparative examples were used to prepare soft-pack batteries, the positive electrode was lithium iron phosphate, the negative electrode was a graphite system, and the nominal capacity of the soft-pack batteries was 2.3 Ah, and electrochemical tests were performed.
[0076] Diaphragm thermal conductivity test: The diaphragms prepared in different embodiments and comparative examples were tested using a heat flow meter. During the test, multiple layers of diaphragms were stacked into a test sample of 1-2 mm, and the test pressure was 10 psi to reduce the contact thermal resistance caused by the stacking of multiple layers.
[0077] Expansion force test during charging and discharging: A pressure sensor is used to monitor the change in expansion force of the battery cell during charging and discharging. The initial expansion force of the battery cell is 100 kgf. The maximum expansion force of the battery cell assembled with the diaphragms prepared in each embodiment and the comparative example during charging and discharging is compared.
[0078] Maximum temperature test during battery cell charging and discharging: The ambient temperature during the test is 25°C. A temperature sensing wire is attached to the large surface of the battery cell to record the temperature rise of the battery cell after charging and discharging.
[0079] The above test results are shown in Table 1.
[0080] Table 1
[0081]
[0082] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0083] The present application can improve the composite effect between the silane-modified base film, the silane-modified inorganic particles and the elastic polymer by silane-modifying the base film and the inorganic particles respectively in step S1. The modified base film of the above type is added to the raw material in step S2, which has the characteristics of high strength and good processing performance. The elastic polymer of the above type has extremely high elasticity and high elongation. It can quickly recover to its original length during the stretching process. The elastic polymer is compounded with the modified base film, which can improve the resilience of the diaphragm while ensuring the strength of the diaphragm, thereby alleviating the excessive expansion force and bulging of the battery cell caused by volume expansion during overcharging of the lithium-ion battery during charge and discharge, and can also relax the design group margin and improve the energy density of the battery cell. It is preferred that the elastic polymer is the above-mentioned polyurethane polymer, which can further improve the resilience of the diaphragm and better compound with the modified base film and the modified inorganic particles. The thermal conductivity of the modified inorganic particles is in the above range, which is much greater than the thermal conductivity of the base film (0.13~0.5W / (m·K)). Therefore, the addition of the modified inorganic particles can greatly improve the thermal conductivity of the diaphragm. Specifically, the modified inorganic particles can effectively conduct the heat of the battery cell during the charging and discharging process, thereby reducing the battery cell performance degradation caused by temperature concentration during the battery cell testing process, and can also reduce the risk of fire and explosion of the battery cell during thermal runaway. The addition of a chain extender can increase the length and cross-linking density of the polymer chain, thereby improving the performance of the diaphragm. The electrospinning process of step S3 can better regulate the morphology, structure and performance of the diaphragm. Therefore, the diaphragm obtained by the preparation method of the present application has high elasticity and high thermal conductivity, which provides a material basis for designing high energy density and safe lithium-ion batteries.
[0084] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a secondary battery separator, characterized in that: The preparation method comprises: Step S1, performing silane modification on the base film and the inorganic particles respectively to obtain a modified base film and modified inorganic particles; Step S2, mixing the raw materials including the elastic polymer, the modified inorganic particles, the modified base film, the chain extender and the organic solvent to obtain a spinning precursor solution; Step S3, electrospinning the spinning precursor solution to obtain the diaphragm; Wherein, the base film is polyethylene and / or polypropylene; The elastic polymer is a polyurethane polymer; The thermal conductivity of the modified inorganic particles is 35-200 W / (m·K); The inorganic particles are aluminum oxide and / or aluminum nitride; when the inorganic particles are a combination of aluminum oxide and aluminum nitride, the mass ratio of the aluminum oxide to the aluminum nitride is 1:1 to 1:2; And / or, the chemical formula of the polyurethane polymer is , where n is 10~35.
2. The preparation method according to claim 1, characterized in that: In the step S2, the mass ratio of the modified base film, the modified inorganic particles and the elastic polymer is 50-75:5-10:25-40.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the elastic polymer to the modified base film is 25-35:55-70; and / or the elongation of the elastic polymer is 400-700%.
4. The preparation method according to any one of claims 1 to 3, characterized in that The step S1 further comprises: ball-milling the inorganic particles to obtain ball-milled particles; The ball-milled particles are mixed with water and then centrifuged and dispersed, washed and dried for the first time to obtain pretreated inorganic particles; Wherein, the rotation speed of the ball mill is 500-600 r / min, and / or the time of the ball mill is 12-20 h; And / or, the first drying temperature is 80-100° C., and / or, the first drying time is 24-36 hours.
5. The preparation method according to claim 4, characterized in that: The step S1 further comprises: using a silane coupling agent to modify the base film and the pretreated inorganic particles respectively, wherein the modification treatment comprises the silane modification and the second drying performed in sequence; Wherein, the silane coupling agent is selected from any one or more of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane; and / or, the temperature of the silane modification is 80-150° C., and the silane modification time is 4-6 hours; And / or, the temperature of the second drying is 100-130° C., and / or, the time of the second drying is 2-4 hours.
6. The preparation method according to any one of claims 1 to 3, characterized in that: In the step S2, the method for preparing the elastic polymer comprises: The polytetrahydrofuran ether diol is sequentially subjected to a first heating, a first vacuum dehydration and a cooling to obtain a pretreated polytetrahydrofuran ether diol; The pretreated polytetramethylene ether diol and diphenylmethane diisocyanate are polymerized to obtain the elastic polymer; Wherein, the molecular weight of the polytetramethylene ether diol is 1000-3000; and / or, the temperature of the first heating is 110-120° C.; and / or, the negative pressure of the first vacuum dehydration is 0.1-0.3 MPa, and the time of the first vacuum dehydration is 2-4 h; and / or, the temperature of the cooling is 60-80° C.; And / or, the polymerization reaction temperature is 80-100° C., and the polymerization reaction time is 40-100 min; And / or, the molar ratio of the pretreated polytetramethylene ether diol to the diphenylmethane diisocyanate is 2-4:
1.
7. The preparation method according to any one of claims 1 to 3, characterized in that The step S2 further comprises: sequentially subjecting the raw materials including the elastic polymer, the modified inorganic particles, the modified base film and the organic solvent to a second heating and a second vacuum dehydration to obtain a first mixture; The raw materials including the first mixture and the chain extender are stirred, degassed and centrifuged in sequence to obtain the spinning precursor solution; Wherein, the organic solvent is N,N-dimethylacetamide; and / or, the temperature of the second heating is 75-85° C.; and / or, the negative pressure of the second vacuum dehydration is 0.1-0.3 MPa, and the time of the second vacuum dehydration is 1.5-4; And / or, the mass ratio of the first mixture to the chain extender is 97~99:1~3; and / or, the chain extender is a diamine compound, and the diamine compound is selected from any one or more of ethylenediamine, 3,3-dichloro-4'-diaminodiphenylmethane and hydroxypropyl acrylate; and / or, the stirring speed is 3000~5000rpm, and the stirring time is 10~20min.
8. The preparation method according to any one of claims 1 to 3, characterized in that: In the step S2, the ratio of the total mass of the elastic polymer, the modified inorganic particles and the modified base film to the volume of the organic solvent is 20-40:100 g / mL.
9. The preparation method according to any one of claims 1 to 3, characterized in that: In the step S3, the spinning precursor solution is sucked into a needle tube for electrospinning; wherein the suction speed is 0.3-0.6 mL / h; and / or the voltage of the electrospinning is 18-25 kV, and / or the spinning roller speed of the electrospinning is 200-300 r / min.
10. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, characterized in that: The separator is obtained by the preparation method according to any one of claims 1 to 9, and the thickness of the separator is 12 to 15 μm.
Citation Information
Patent Citations
Composite microporous membrane used as lithium ion battery diaphragm as well as preparation method and application thereof
CN102122704A
Method for preparing multilayer composite membrane for secondary battery by using electrostatic spinning coating method
CN102779964A
A battery separator and a preparation method thereof
CN109103396A
Flexible ceramic fiber membrane reinforced perfluorinated proton exchange membrane and preparation method thereof
CN110828870A
Lithium battery diaphragm and preparation method thereof
CN112787042A